CO2 Embodied in Trade between Poland and Selected Countries - Mizgajski, Jan T. (Journal of Economic Development, Environment and People, 2013)
This study is aimed at analysing the carbon embodied in trade flows between Poland and its major trade partners. Calculations are based on the data from the GTAP database for the year 2004. The study uses an input-output analysis, which allows responsibility to be assigned to individual flows for generating specific amounts of emissions in the economy. It is shown that Polish exports contain significantly more embodied carbon than Polish imports, despite the fact that the value of the imports is higher. Moreover, it is found that among the surveyed countries, only three were net importers of carbon emissions to Poland. Export to Germany is responsible for the most of emissions in Poland. In turn, Poland receives the most emissions from imports from Russia.